Respostas

2014-08-05T18:25:45-03:00
Me ajudeeem nessa equação
 
  x² - 2x 
-------------  =  1
  3x - 6


1(x² -2x)  =  1(3x - 6)
------------------------------    fração com igualdade desprezamos o denominador
       3x - 6

1(x² - 2x) = 1(3x-6)
x² - 2x = 3x - 6------------------------igualar a ZERO
X² - 2X - 3X + 6 = 0
x² - 5x + 6 = 0
a = 1
b = - 5
c = 6
Δ = b² - 4ac
Δ = (-5)² - 4(1)(6)
Δ = 25 - 24
Δ = 1-------------------------√1 = 1---------------√Δ = 1
se
Δ > 0 duas raízes diferentes
então
(baskara)
x = - b - + 
√Δ/2a

x' = -(-5) - 
√1/2(1)
x' = + 5 - 1/2
x' = 4/2
x' = 2
e
x" = -(-5) + 
√1/2(1)
x" = + 5 + 1/2
x" = 6/2
x" = 3

V = {2;3}